Risk factors associated with iron deficiency anemia in older adults - Mendoza Orcon, Kevin B. (2022)
Objective: To carry out a systematic review of various scientific publications about the risk factors associated with iron deficiency anemia in older adults. Methods: The review was carried out through the electronic search of various scientific articles related to the subject. The PEO question was used: what is the association between risk factors and iron deficiency anemia in older adults? The search source was PubMed. Articles published from January 1, 2016, to 2021 were selected. Results: Of the 223 articles found, 212 were discarded because they did not meet the inclusion and exclusion criteria, therefore, 11 articles remained for this review. Conclusion: Various intrinsic and extrinsic risk factors are associated with the acquisition of iron deficiency anemia or iron deficiency in elderly patients.